2014
DOI: 10.3989/scimar.03942.30b
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary evaluation of landings and discards of the Turkish bottom trawl fishery in the northeastern Aegean Sea (eastern Mediterranean)

Abstract: Summary: This short-term study on commercial discards was carried out in fishing grounds around Gökçeada Island in the northeastern Aegean Sea, a geographic area where fisheries information is rather limited. A total of 28 bottom trawls were performed between 70 and 410 m depth from December 2009 to February 2010. All the samples were collected on board a commercial trawler under commercial fishing conditions. A total of 3143 kg of biomass was caught in 28 valid hauls. Landings accounted for about 67% of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 48 publications
2
5
0
Order By: Relevance
“…Thus, the use of 40S net triggers fishers to include less illegal sizes in landings and therefore act with more compliance to the existing regulations. Machias et al (2004), Damalas and Vassilopoulou (2013) and Keskin et al (2014), based on onboard observations, found also undersized hake in landings as in our case. Moreover, Tsagarakis et al (2017) mentioned that among various Mediterranean countries hake size at which 50% is discarded (or retained) ranges between 10-17 cm.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Thus, the use of 40S net triggers fishers to include less illegal sizes in landings and therefore act with more compliance to the existing regulations. Machias et al (2004), Damalas and Vassilopoulou (2013) and Keskin et al (2014), based on onboard observations, found also undersized hake in landings as in our case. Moreover, Tsagarakis et al (2017) mentioned that among various Mediterranean countries hake size at which 50% is discarded (or retained) ranges between 10-17 cm.…”
Section: Discussionsupporting
confidence: 83%
“…Fishers may land undersized catch (as in the case of hake), but also may land much larger fish than the LFM (as in the case of horse mackerel and megrim) depending on the species and their marketability. This was also suggested by Machias et al (2004), Damalas and Vassilopoulou (2013), Keskin et al (2014), Bellido et al (2014 and Tsagarakis et al (2014Tsagarakis et al ( , 2017 for the Mediterranean fishery. These findings may imply for more compliance to the legislated MLS as in the case of hake.…”
Section: Discussionsupporting
confidence: 65%
“…All three species appeared uncommon in Greek waters, in the 1990s and 2000s, as observed in surveys (Bertrand et al, ; Tserpes, Maravelias, Pantazi, & Peristeraki, ) and fisheries catch data (Damalas & Vassilopoulou, ; Megalofonou et al, ). Along the Turkish coast, where old records were not found, recent data from local small surveys or fisheries catches showed that MUSP is still very common (Ismen, Cigdem Yigin, Altinagac, & Ayaz, ; Kabasakal, ; Keskin, Ordines, Ates, Moranta, & Massutí, ; Torcu & Aka, ).…”
Section: Resultsmentioning
confidence: 99%
“…A considerable proportion of the unknown tracks overlapping known fishing hotspots lasted no more than 2 h and their mean speed was 2-5 kn. Since these values are typical of the fishing operations of most Mediterranean bottom trawlers (Lucchetti, 2008;Lambert et al, 2012;Keskin et al, 2014;Arjona-Camas et al, 2019), this subset was felt to represent hidden fishing and was used to sketch a more realistic picture of the overall fishing activity.…”
Section: Discussionmentioning
confidence: 99%